The influence of public policies on municipal management of solid waste recycling: A systematic review - Silva, Nathália de Jesus Vieira; Almeida, Emerson Gervásio de (Seven Editora, 2024)
This systematic study of the literature aims to demonstrate the state of the art regarding the productions of the administrative niche that deals with environmental public policies and solid waste recycling management. From the systematization, it is possible to delineate the collection on the theme that in recent decades has been treated with more recurrence due to the historical context of consumption and unbridled disposal. This theme, which is problematic in this review, allows us to reflect on the need for effective actions to mitigate the environmental impacts of urban solid waste, arising from uncontrolled production and disposal. Public policies, actions that promote sustainability practices, enable the public-private relationship in order to provide national organizations with the opportunity to promote the proper recycling of their waste, generating profitability from consumption and/or assisting with the correct disposal, becoming an active part in the process of mitigating damage to the environment. Formalized through the National Solid Waste Policy (PNRS), published in 2010, the actions that aim at a balanced environment, such as selective collection and recycling, were systematized in this legislative plan where the importance of the adoption by municipalities of sustainable actions regarding discarded solid waste is emphasized. The PNRS, when achieved, provides benefits as a whole, since it is the balanced environment that provides raw material for moving the economy, and it is necessary to reduce the volumes sent to landfills, extinguish irregular deposition, valorization and reinsertion of waste in the production chain, reduce the need to use natural resources and other measures proposed by this Policy; which must be applied from sustainable municipal management. DOI:https://doi.org/10.56238/sevened2024.014-025